Analisis Gaya Belajar Siswa pada Mata Pelajaran Bahasa Indonesia Siswa Kelas IV SD N 1 Cempaga - Saputri, Ni Kadek Tina; Numertayasa, I Wayan; Astuti, Ni Putu Eni (AS-SABIQUN, 2024)
This research examines "Analysis of Student Learning Styles in Class IV Indonesian Language Subjects at SD N 1 Cempaga". The aim of the research is to determine visual, auditory and kinesthetic learning styles, especially for class IV students in Indonesian Language subjects. This research used a qualitative method with the number of informants being 20 students. Data collection techniques are observation, interviews and documentation. The data analysis technique uses the Milles and Hubberman model, namely the technique of collecting data, reducing data, presenting data and drawing conclusions or reducing data. The results of the research found were that students' learning styles in the Indonesian language subject of class IV students at SD N 1 showed that there was a combination of VAK learning styles (Visual, Auditory and Kinesthetic). However, the tendency of each student is different, namely the learning style is a visual learning style with 50% or 10 students out of 20 students. Auditory learning style is 10% d or 2 students out of 20 students, and kinesthetic learning style is 40% or 8 students out of 20 students.